Development of albumen rich ready to eat coagulated egg product - Prasad, Kamlesh; Lovina; Shekhar , Shubhra (Journal of Postharvest Technology, 2024)
Development of albumen rich RTE coagulated egg product was carried out using blends of albumen with yolk and different spices at optimum temperature and time combination of 92.77˚C/12 min which was optimized in earlier studies using response surface methodology. Result showed that based on sensory scores on nine-point hedonic scale, red chili powder and cardamom were the only spices compatible with the albumen. Optimized RTE coagulated egg product could be obtained from the yolk free egg with spice mix at the rate of 0.3%..